Perkembangan Pasar Tradisional Pancur Batu di Deli (1960-1975) - Eva Angelia Sembiring; Pujiati; Fikarwin Zuska (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2023)
This research uses a historical method consisting of heuristic stages, verification, interpretation and historiography, and uses a socioeconomic approach to explain chronologically the presence of the Pancur Batu market which then brings its development and influence on the welfare of the local community. The results showed that Pancur Batu Market was present since its area became part of the Deli tobacco plantation area centered in East Sumatra in 1872. The development was even more crowded in 1960 when a proposal was made by local residents to the regional government of Deli Hulu regarding the construction and expansion of the Pancur Batu market area in the form of adding stalls and los. In addition, the development of the Pancur Batu Market then has a significant influence on the negative direction in the form of traffic congestion because the Pancur Batu area is a link between the highlands and low flats and the condition of market waste is increasing, but from the positive side, there is a harmony of inter-ethnic relations in Pancur Batu and the increasing income of the population. Keywords: Pancur Batu, distribution of goods, market influence